2006
DOI: 10.1111/j.1365-2214.2006.00603.x
|View full text |Cite
|
Sign up to set email alerts
|

Authoritative parenting and parental stress in parents of pre‐school and older children with developmental disabilities

Abstract: Findings suggest that the well-established effect of group on stress may be moderated by parenting style. Authoritative parenting may be highly stressful for parents of children with DD to implement, resulting in a decrease in its use across the two age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
59
2
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 46 publications
8
59
2
5
Order By: Relevance
“…Pascoe et al [16] found that social network communication and supportiveness correlated positively with the psychical organization of the child's world, and with mothers' avoidance of punishment, nag, and restriction, which is inconsistent with the present study. Belsky [3,9] viewed the marital relationship as one of the potential sources of support in the parenting process.…”
Section: Discussioncontrasting
confidence: 99%
“…Pascoe et al [16] found that social network communication and supportiveness correlated positively with the psychical organization of the child's world, and with mothers' avoidance of punishment, nag, and restriction, which is inconsistent with the present study. Belsky [3,9] viewed the marital relationship as one of the potential sources of support in the parenting process.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition the results of this study reiterate the role that maternal parenting stress plays in parenting styles and that high maternal stress is related to more inconsistent and punitive, and less positive parenting styles (Wolfson & Grant, 2006). Finally, these data suggest that a child's temperamental style (in particular their self regulatory skills) uniquely impacts upon their level of impairment both directly, and indirectly through increasing parenting stress.…”
Section: Discussionsupporting
confidence: 58%
“…Wolfson and Grant (2006) found that, among mothers of children with developmental difficulties, high parenting stress was associated with a more authoritarian parenting style, suggesting that high stress as a result of their child's difficult behaviour, may impact upon the level of negative control used by parents of difficult children. Therefore, because difficult children elicit more stress and negative control, and negative parental control has been associated with adverse trajectories in disruptive preschool children (Campbell et al, 2000) it is likely that a child's ADHD symptom severity, as well as their temperament, will influence how parents interact with their child (e.g.…”
mentioning
confidence: 98%
“…Research has suggested that parents around the world who have a child with IDD experience significantly more stress than parents of typically developing children (Kumar 2008;Richman Belmont et al 2009;Woolfson and Grant 2005). In a sample of mothers of children with intellectual disabilities in India, 75 % reported clinically significant levels of stress (John 2012).…”
Section: Introductionmentioning
confidence: 99%